Some common fixed point theorems for weakly compatible mappings on cone Banach space (Letters in Nonlinear Analysis and its Applications, 2025)
The primary objective of this paper is to establish the existence of coincidence points and common fixed points for $N \in \mathbb N $ self-mappings defined on cone Banach spaces under the framework of weak compatibility. By employing an ordered structure and suitable contractive conditions, we present general fixed point results that extend and unify several known theorems in the existing literature. Specifically, Theorem 2, 3 and 4 address the existence of coincidence and common fixed points for eight, six, and four self-mappings, respectively. Our findings contribute to the ongoing development of fixed point theory in cone metric spaces, offering broad generalizations and encompassing a wide range of previously established results as special cases.